Ragam Fungsiolek Bahasa Penyiar Radio SIPP FM Padang: Suatu Tinjauan Sosiolinguistik - Ena Noveria (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2008)
As means of communication, language is an important element in mass media such as radio. Radio also has important role in the language construction and development. However, broadcasters tend to use informal language to interact with the youngster. This research is aimed at identifying the language used by broadcasters in SIPP FM Padang related to the reading method at “Simak Bebas Libat Cakap (SBLC)”. In short, this paper is expected to give contribution to the broadcasters to use language correctly. Keywords: functional dialect, broadcasters, language